Social exclusion and labour market outcomes: evidence from eastern Europe and central Asia - Bangwayo-Skeete, P.F.; Zikhali, Precious (Emerald Publishing Limited, 2011)
Purpose - The paper seeks to examine the impact of social exclusion on individuals' propensity to be employed and how, if employed, social exclusion affects individuals' perceived job insecurity and the likelihood of being covered by social insurance in their jobs. Design/methodology/approach - Using the United Nations Development Program/United Nations Children Fund 2009 survey data from Eastern Europe and Central Asia, the paper employs comprehensive econometric methods that overcome challenges posed by endogeneity of social exclusion in labour market outcomes, self-selection into employment, and the interdependency between perceptions of job security and social insurance coverage. Findings - Results suggest that socially excluded individuals face hurdles in securing jobs and exhibit higher risk of job loss. Further, results suggest that a holistic educational policy could help promote social inclusion. Practical implications - Formulation of policies aimed at promoting social inclusion and improved labour market outcomes should not be done in isolation; rather they should be based on a holistic understanding of the multi-faceted nature of social exclusion. Originality/value - The originality of the analysis is that it takes into account the multi-dimensional nature of social exclusion by treating social exclusion as an outcome of a diverse set of an individual's socio-economic characteristics that ultimately shape the way they feel about their exclusion or inclusion in their societies. This gives an indication of the types of people that are socially excluded and form the group for which a further investigation of labour market outcomes is conducted.